In vitro evaluation of poly (lactic acid-co-glycolic acid)/ atelocollagen/fibrin bioscaffold for annulus fibrosus regeneration - Mohamad, Mohd Yusof; Mohamed Amin, Muhammad Azri Ifwat; Zulkifly, Ahmad Hafiz; Sha'ban, Munirah (Society for Biomaterials and Artificial Organs - India, 2020)
The current study evaluated the 3D culture of the PLGA incorporated with atelocollagen and fibrin seeded with the annulus cells of intervertebral disc. The evaluation was performed in three consecutive weeks observing at the morphology, compression modulus, histology, immunohistology, sulphated glycosaminoglycan (SGAG) and DNA content. A comparison was made between the AF seeded onto the PLGA (PLGA-AF), PLGA with atelocollagen (PAAF), PLGA with fibrin (PF-AF) and PLGA with both atelocollagen and fibrin (PAF-AF). The constructs displayed glistening morphology with high wet weight and cellular viability by week 3. The PAF-AF and PA-AF demonstrated significant compression modulus. The presence of collagen type I were detected in all the constructs. The histological findings showed extensive AF cellular distribution. Significant quantitative sGAG was detected for the PAF-AF constructs but with no significant differences on the DNA content. Overall, the PAF-AF constructs support the cellular proliferation of the AF